2016
DOI: 10.1111/gbb.12321
|View full text |Cite
|
Sign up to set email alerts
|

GABAA receptor subtype involvement in addictive behaviour

Abstract: GABA A receptors form the major class of inhibitory neurotransmitter receptors in the mammalian brain. This review sets out to summarize the evidence that variations in genes encoding GABA A receptor isoforms are associated with aspects of addictive behaviour in humans, while animal models of addictive behaviour also implicate certain subtypes of GABA A receptor. In addition to outlining the evidence for the involvement of specific subtypes in addiction, we summarize the particular contributions of these isofo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 338 publications
(740 reference statements)
3
74
0
Order By: Relevance
“…Inhibitory gamma-aminobutyric acid (GABA)ergic neurotransmission is Yin to the excitatory glutamatergic Yang of brain signaling. Like glutamate and the NMDA receptor, the GABA system is highly sensitive to alcohol and other drugs of abuse, as discussed in a comprehensive review by Stephens et al (2016). The authors introduce a preclinical literature that has aimed to dissect the relative functional roles of GABA A receptors with differing subunit compositions and relate this to work in humans that identifies a significant genetic association between various subunits (e.g.…”
mentioning
confidence: 99%
“…Inhibitory gamma-aminobutyric acid (GABA)ergic neurotransmission is Yin to the excitatory glutamatergic Yang of brain signaling. Like glutamate and the NMDA receptor, the GABA system is highly sensitive to alcohol and other drugs of abuse, as discussed in a comprehensive review by Stephens et al (2016). The authors introduce a preclinical literature that has aimed to dissect the relative functional roles of GABA A receptors with differing subunit compositions and relate this to work in humans that identifies a significant genetic association between various subunits (e.g.…”
mentioning
confidence: 99%
“…In common with thalamus and cortex, it can synthesise GABA A R‐active neurosteroids (unpublished observations ‐ Mitchell SJ, Maguire EP, Belelli D, Lambert JJ). Furthermore, we find that adult mice previously exposed to ELS, exhibit altered accumbal GABA A R neurotransmission and an abnormal response to cocaine (ie, an altered locomotor sensitisation), a behaviour that recapitulates in rodents aspects of drug addiction …”
Section: Neurosteroids Early‐life Adversity and Psychiatric Disordersmentioning
confidence: 78%
“…Furthermore, we find that adult mice previously exposed to ELS, exhibit altered accumbal GABA A R neurotransmission and an abnormal response to cocaine (ie, an altered locomotor sensitisation), a behaviour that recapitulates in rodents aspects of drug addiction. 140 Schizophrenia is negatively influenced by early-life adversity. [141][142][143] The findings by Grobin et al, 115,116 as discussed above, suggest a possible link between early neurosteroid dysregulation and an abnormal developmental pattern for prefrontal cortex, a region implicated in schizophrenia.…”
Section: Neurosteroids Early-life Adversity and Psychiatric Disordersmentioning
confidence: 99%
“…The other genes in the distal chromosome 15q11.2‐q13 region include gamma aminobutyric acid (GABA) receptor subunits GABRB3, GABRA5 , and GABRG3 , which are not imprinted. Alterations in the GABAergic systems are associated with hunger (Turenius et al, ), anxiety (Hodges et al, ), OC symptoms, and addiction (Stephens, King, Lambert, Belelli, & Duka, ). While hypoactivity may contribute to obesity in PWS (Dhar et al, ), nearly 60% of our patients were reported to be hyperactive and perhaps this sheds some light on differences in metabolic phenotype in AS compared to PWS.…”
Section: Discussionmentioning
confidence: 99%